Preliminary step towards renal nomogram in Malaysian adult population - Supriyanto, Eko (2011)
Renal ultrasonography is a relatively inexpensive, fast, non-invasive and radiation-free imaging modality to diagnose a range of kidney diseases. Variation in kidney sizes can be associated with different kidney diseases. Commonly, measurements of renal size of any age are compared with the measurements that are predicted by standard nomograms. However, the current nomograms which are widely used locally are derived from studies based on western population of relatively small sample sizes. Therefore, there is an urge in developing our own Malaysian population nomogram to provide a better accuracy of renal measurements in terms of making a proper medical diagnosis. This study analysed 200 kidney samples after taking ultrasonic images from normal adult Malaysian population. The renal parameters analysed were length, width, thickness and volume which were plotted against height, weight and gender of the respondent. Results showed there is a significant direct positive correlation between renal size and body weight. There is not much difference genderwise. The relationship between body weight and height to kidney size also corresponds to other studies that the higher the body weight, the bigger the kidney is.